Світові тенденції розвитку електронної комерції з урахуванням кризових умов пандемії Covid-19 - Бергер, Аліна Дмитрівна; Галета, Андрій Сергійович (My University, 2021)
У статті обґрунтовується актуальність дослідження поширення у світі електронної комерції завдяки наслідкам пандемії Covid-19. Аналіз останніх публікацій з цього питання показав, що світова роздрібна торгівля зазнала суттєвих змін завдяки постійній цифровізації сучасного життя. За світовими прогнозами на 2023 рік зростання електронної комерції в роздрібних продажах досягне 5,9 трильйона доларів США. П’ятіркою лідерів за приростом у роздрібних продажах електронної комерції стануть наступні країни: Китай ‒70,3%, США ‒ 45,7%, Франція ‒ 45,6%, Австралія ‒ 44,6%, Росія ‒ 44,2%. Лідерами у світовому рейтингу веб-сайтів з роздрібної торгівлі за обсягом трафіку є Amazon, Taobao та Tmall. Однією з найбільших тенденцій у світовій електронній комерції є використання мобільних пристроїв як напрямку роздрібної торгівлі, що демонструє перспективне зростання. За прогнозом групи компаній EVO в Україні у 2021 році передбачається, також як у світі, зростання роздрібного електронного комерційного продажу на третину. The actuality of the research of world electronic commerce distribution due to the consequences of COVID - 19pandemic is established in the article. Publications for 2020 of electronic commerce issues testify to their variety, multitasking nature and specific directions. The analysis of open sources of this question showed, that the world retail business had tested substantial changes due to permanent digitalization of modern life and consumers have possibilities to get income in on-line business. The amount of digital technologies customers in the world grows annually. In 2020 the volumes of the world electronic retail exceeded 4,9 trillions of USA. On the world prognoses on 2023 the increase of electronic commerce in retails will attain 5,9 trillions of USA dollars. Five leaders after the increase of electronic commerce in retails will be the following countries: China ‒ 70,3%, USA ‒ 45,7%, France ‒ 45,6%, Australia ‒ 44,6%, Russia ‒ 44,2%. Leaders in the world rating of web sites of retail business by traffic is Amazon on Taobao and Tmall. One of the biggest tendencies in the world electronic commerce is the use of mobile devices as the direction of retail business that demonstrates perspective increase. M-commerce is especially popular in the countries of Asia, such as South Korea, where generate to 65 % of general volume of online-transactions by means of mobile traffic. Influence of Covid - 19 pandemic on the Internet-traffic from the side of sale volumes, testifies to its substantial increase in behalf on supermarkets, Medias and television. Influence of pandemic on transaction from the side of sale volumes in the cut of industries testifies to their substantial increase in retail business, medical insurance, bank, cosmetic spheres. Analogical tendencies in the development of electronic commerce in the conditions of pandemic to the coronaviruses are observed also in Ukraine. In 2020 in Ukraine the total amount of commodities and services that purchased consumers in the Internet increased on 41% than it previous year. Thus, on the prognosis of EVO group the companies in 2021 the increase of electronic commercial retail is envisaged on one third.
Keywords: кафедра маркетингу; електронна комерція; тенденції; пандемія Covid-19; наслідки; зміни; криза; продажі; м-комерція; E-commerce; trends; pandemic Covid-19; consequences; changes; crisis; sales; M-commerce